Cytoprotective effects of fermented oyster extracts against oxidative stress-induced DNA damage and apoptosis through activation of the Nrf2/HO-1 signaling pathway in MC3T3-E1 osteoblasts - Park, Cheol; Lee, Hyesook; Han, Min Ho; Jeong, Jin-Woo; Kim, Sung Ok; Jeong, Soon-Jeong; Lee, Bae‐Jin; Kim, Gi‐Young; Park, Eui Kyun; Jeon, You‐Jin; Choi, Yung Hyun (IfADo - Leibniz Research Centre for Working Environment and Human Factors, Dortmund, 2020)
Osteoblast damage by oxidative stress has been recognized as a cause of bone-related disease, including osteoporosis. Recently, we reported that fermented Pacific oyster (Crassostrea gigas) extracts (FO) inhibited osteoclastogenesis and osteoporosis, while promoting osteogenesis. However, since the beneficial potential of FO on osteoblasts is not well known, in the present study, we investigated the cytoprotective effect of FO against oxidative stress in MC3T3-E1 osteoblasts. Our results demonstrated that FO inhibited hydrogen peroxide (H2O2)-induced DNA damage and cytotoxicity through the rescue of mitochondrial function by blocking abnormal ROS accumulation. FO also prevented apoptosis by suppressing loss of mitochondrial membrane potential and cytosolic release of cytochrome c, decreasing the rate of Bax/Bcl-2 expression and reducing the activity of caspase-9 and caspase-3 in H2O2-stimulated MC3T3-E1 osteoblasts, suggesting that FO protected MC3T3-E1 osteoblasts from the induction of caspase dependent- and mitochondria-mediated apoptosis by oxidative stress. In addition, FO markedly promoted the activation of nuclear factor-erythroid-2-related factor 2 (Nrf2), which was associated with the enhanced expression of heme oxygenase-1 (HO-1). However, inhibiting the expression of HO-1 by artificially blocking the expression of Nrf2 using siRNA significantly eliminated the protective effect of FO, indicating that FO activates the Nrf2/HO-1 signaling pathway in MC3T3-E1 osteoblasts to protect against oxidative stress. Based on the present data, FO is thought to be useful as a potential therapeutic agent for the inhibition of oxidative stress in osteoblasts. : EXCLI Journal; 19:Doc1102; ISSN 1611-2156